MODEL PREDIKSI GELOMBANG TERBANGKIT ANGIN DI PERAIRAN SEBELAH BARAT KOTA TARAKAN BERDASARKAN DATA VEKTOR ANGIN - Roem, Muhamad; ., Ibrahim; Alamsyah, Nur (Jurnal Harpodon Borneo, 2015)
The study was carry out to describe the wave driven by wind blows at the west side of Tarakan Waters. The modelling analysis using BMKG data which analysed by WRPLOT. From this study we conclude that West Side of Tarakan Water is dominated by wave taht come from west and northwest. The maximum wave height that may hit the west coast of Tarakan is 1,4 m with the probability value only 8,3 %.  Keywords : Wind waves, Tarakan.